Metal-seed planting fabrication of W–W18O49 core shell nanoflowers for gas sensors - Luo, Jianyi; Li, Yudong; Mo, Xiwei; Xu, Youxin; Zeng, Qingguang (RSC advances, 2017)
In this study, a new kind of metal oxide nanoflower has been controllably synthesized on pre-designed regions of a substrate by a metal-seed planting method, in which the nanoflowers only appear where the metal seeds are planted. The material characterization technologies have proved that such nanoflowers are composed of a nanowire shell and a nanoparticle core, and their structures can be assigned to monoclinic W18O49 and cubic W phases, respectively. The growth mechanism of the W–W18O49 core shell nanoflowers has also been investigated by recording the growth process from the metal-seed W particles to the nanoflowers in the metal planting method. Furthermore, after annealing in air, the W–W18O49 nanoflowers were completely oxidized into WO3 nanoflowers, the hydrogen gas sensor based on a Pt coated WO3 (Pt–WO3) nanoflower film was fabricated, and the gas sensing test showed that it is a potential material to resolve the unstable sensing performance of normal metal oxide sensors at room temperature.